Environmental sustainability in Indonesian pesantren: Integrating pious principles and da’wah efforts - Alam, Lukis; Alam, Meredian; Samaalee, Abdunrorma; Suyatno, Suyatno (Jurnal Ilmu Dakwah, 2024)
Purpose - This article examined the role of environmentalism within Java pesantren, Indonesia, focusing on how faith-based teachings and da’wah can support sustainability practices. Method - The article focuses on the pesantren communities in Java, Indonesia. It employs a qualitative that incorporates fieldwork and document analysis to investigate the interplay between environmental consciousness, religious instruction, and sustainable practices. Data was gathered through in-depth interviews and participant observation involving pesantren leaders, educators, and students, offering a comprehensive insight into the community. Result  -  The article's findings indicate a significant impact of religious teachings on environmental awareness and sustainable practices within pesantren. Environmental efforts, implicitly tied to da’wah and rooted in spiritual principles, positively influence the inclination of students and community members to engage in sustainability initiatives. Implication – The article shows that including faith-based education and dawah in environmental practices can greatly support sustainability efforts in faith-based institutions. This integration is essential for raising environmental awareness and encouraging proactive measures among community members. Originality - As an original attempt, this research eludates environmental awareness into understanding the influence of religious instruction, implicitly through da’wah, on sustainable practices within pesantren communities.*** Tujuan - Artikel ini mengkaji peran lingkungan hidup dalam pesantren di Jawa, Indonesia, dengan fokus pada bagaimana ajaran berbasis keagamaan dan da’wah dapat mendukung praktik keberlanjutan pelestarian lingkungan. Metode- Artikel ini berfokus pada komunitas pesantren di Jawa, Indonesia. Penelitian ini menggunakan pendekatan kualitatif yang melibatkan kerja lapangan dan analisis dokumen untuk menyelidiki keterkaitan antara kesadaran lingkungan, pengajaran agama, dan praktik berkelanjutan. Data dikumpulkan melalui wawancara mendalam dan observasi partisipatif yang melibatkan para pemimpin pesantren, pendidik, dan santri, sehingga memberikan wawasan yang komprehensif tentang komunitas tersebut. Hasil  -  Artikel mencermati pengajaran agama terhadap kesadaran lingkungan dan praktik berkelanjutan pelestarian lingkungan di dalam pesantren. Pengajaran dan dakwah terkait dengan prinsip-prinsip keislaman dan spiritualitas telah mempengaruhi prinsip dan perilaku santri serta  masyarakat di pesantren untuk terlibat keberlanjutan pelestarian lingkungan. Implikasi – Kontribusi artikel ini mendorong pesantren di Jawa, Indonesia sebagai lembaga yang konsisten dalam pengajaran keislaman dan dakwah untuk senantiasa menginisiasi kesadaran lingkungan. Proses ini penting karena menjadi instrumen utama dalam melihat dan memahami tentang pentingnya menjaga dan melestarikan lingkungan Orisinalitas/Nilai- Riset ini orisinal dalam mengurai kesadaran lingkungan yang didasarkan atas praktik dan pengajaran keislaman serta aktivitas da’wah di komunitas pesantren.